ANALISIS KESULITAN SISWA KELAS XI-MIPA PADA MATERI TRIGONOMETRI DI SMA N 1 KECAMATAN GUNUANG OMEH - Nova Novita; Isnaniah Isnaniah; Defri Joni (Universitas Pahlawan Tuanku Tambusai, 2022)
The learning outcomes of students in class XI at SMA N 1 Gunuang Omeh District on trigonometric material are still below the Minimum Completion Criteria (KKM) and the PH 1 mathematics score in class XI-MIPA for the 2022/2023 Academic Year on trigonometric material is still low. The purpose of this study is to determine the types of learning difficulties experienced by students in trigonometric material in mathematics learning. The method used in this study is a descriptive type qualitative approach. The subjects of this study were 6 out of 29 students of class XI-MIPA at SMA N 1 Gunuang Omeh District in the 2022/2023 academic year. Data collection using tests and through interviews. The test is carried out as one of the considerations in the taking of the subject and to map the learning difficulties of students in trigonometric material. Meanwhile, interviews were conducted to identify the difficulties experienced by students in learning trigonometric material. The difficulty experienced by students in using concepts is caused because students do not understand in defining concepts that exist in trigonometric material (sine, cosine, and tangents). The difficulty of students in understanding the principle used is due to the difficulty in students in calculating operations, students are unable to determine the comparative value at a privileged angle in trigonometric material. Then, students have difficulty in solving problems in verbal form because students have difficulty translating and associating problems with concepts in trigonometry material. Therefore, schools should be able to further strengthen the understanding of basic concepts in mathematics, especially trigonometric materials. Students are able to master the basic concepts for solving a problem in trigonometry, such as basic concepts in the form of roots, pythagorean theorem and trigonometric comparisons in mathematics learning. Keywords: Analysis, Difficulty, Students, Trigonometry, Mathematics